Factors influencing prehospital physicians' decisions to initiate advanced resuscitation for asystolic out-of-hospital cardiac arrest patients. (August 2022) - Gamberini, Lorenzo; Mazzoli, Carlo Alberto; Allegri, Davide; Scquizzato, Tommaso; Baroncini, Simone; Guarnera, Martina; Tartaglione, Marco; Chiarini, Valentina; Picoco, Cosimo; Semeraro, Federico; Gordini, Giovanni; Coniglio, Carlo
Abstract: Background: The decision to initiate or continue advanced life support (ALS) in out-of-hospital cardiac arrest (OHCA) could be difficult due to the lack of information and contextual elements, especially in non-shockable rhythms. This study aims to explore factors associated with clinicians' decision to initiate or continue ALS and the conditions associated with higher variability in asystolic patients. Methods: This retrospective observational study enrolled 2653 asystolic patients on whom either ALS was attempted or not by the emergency medical services (EMS) physician. A multivariable logistic regression analysis was performed to find the factors associated with the decision to access ALS. A subgroup analysis was performed on patients with a predicted probability of ALS between 35% and 65%. The single physician's behaviour was compared to that predicted by the model taking into account the entire agency. Results: Age, location of event, bystander cardiopulmonary resuscitation and EMS-witnessed event were independent factors influencing physicians' choices about ALS. Non-medical OHCA, younger patients, less experienced physicians, presence of breath activity at the emergency call and a longer time for ALS arrival were more frequent among cases with an expected higher variability in behaviours with ALS. Significant variability was detected between physicians. Conclusions: Significant inter-physician variability in access to ALS could be present within the same EMS, especially among less experienced physicians, non-medical OHCA and in presence of signs of life during emergency call. This arbitrariness has been observed and should be properly addressed by EMS team members as it raises ethical issues regarding the disparity in treatment.